2021
DOI: 10.1007/s11274-021-03141-z
|View full text |Cite
|
Sign up to set email alerts
|

A bioprocess perspective on the production of secondary metabolites by Streptomyces in submerged co-cultures

Abstract: Filamentous microorganisms are potent sources of bioactive secondary metabolites, the molecules formed in response to complex environmental signals. The chemical diversity encoded in microbial genomes is only partially revealed by following the standard microbiological approaches. Mimicking the natural stimuli through laboratory co-cultivation is one of the most effective methods of awakening the formation of high-value metabolic products. Whereas the biosynthetic outcomes of co-cultures are reviewed extensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Here, we propose a strategy to screen co-culture microbial combinations by targeting the improvement of antibacterial activity. Interestingly, studies have shown that changes in state of the medium (i.e., solid or liquid), composition (i.e., carbon source and nitrogen source) and culture conditions (i.e., temperature, culture length, and pH), or the addition of some trace elements might lead to improved antibacterial activity ( Boruta et al, 2020 ; Boruta, 2021 ; Gao et al, 2021 ; Sun et al, 2022 ), which provided new strategies to further explore valuable SMs of the co-culture of E. amstelodami and Bacillus species.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we propose a strategy to screen co-culture microbial combinations by targeting the improvement of antibacterial activity. Interestingly, studies have shown that changes in state of the medium (i.e., solid or liquid), composition (i.e., carbon source and nitrogen source) and culture conditions (i.e., temperature, culture length, and pH), or the addition of some trace elements might lead to improved antibacterial activity ( Boruta et al, 2020 ; Boruta, 2021 ; Gao et al, 2021 ; Sun et al, 2022 ), which provided new strategies to further explore valuable SMs of the co-culture of E. amstelodami and Bacillus species.…”
Section: Discussionmentioning
confidence: 99%
“…Unconventional methods are needed to awaken “silent” biosynthetic pathways and induce the production of secondary metabolites. One of the most promising approaches to in vitro cultivation is simulation of the natural interaction between different species of microorganisms by means of co-culturing [ 52 ] to obtain a large variety of secondary metabolites [ 53 ]. In a co-culture, two or more distinct microorganisms are incubated together in order to mimic the natural environment [ 52 , 54 , 55 ].…”
Section: Microbiologymentioning
confidence: 99%
“…Although these biotic induction methods have proven to be fruitful, most studies have been undertaken in a random or empirical manner. Different strains are often simply combined in shake flask cultures, using rich standard cultivation media for Streptomyces sp., as reviewed by Boruta (2021), Maglangit et al (2020), Wakefield et al (2017), and Yu et al (2019). However, in the natural environment, nutrients are typically not very abundant and the resulting nutrient availability greatly influences specialized metabolite production (Doull & Vining, 1990;Scherlach et al, 2011).…”
Section: Introductionmentioning
confidence: 99%